Fire suppression and seed dispersal play critical roles in the establishment of tropical forest tree species in southeastern Africa - Tomohiro Fujita (Nature Portfolio, 2021)
Abstract This study examined the mechanisms of facilitation and importance of seed dispersal during establishment of forest tree species in an Afrotropical woodland. Seedling survival of Syzygium guineense ssp. afromontanum was monitored for 2.5 years at four different microsites in savannah woodland in Malawi (southeastern Africa) under Ficus natalensis (a potential nurse plant), Brachystegia floribunda (a woodland tree), Uapaca kirkiana (a woodland tree), and at a treeless site. The number of naturally established forest tree seedlings in the woodland was also counted. Additionally, S. guineense ssp. afromontanum seed deposition was monitored at the four microsites. Insect damage (9% of the total cause of mortality) and trampling by ungulates (1%) had limited impact on seedling survival in this area. Fire (43%) was found to be the most important cause of seedling mortality and fire induced mortality was especially high under U. kirkiana (74%) and at treeless site (51%). The rate was comparatively low under F. natalensis (4%) and B. floribunda (23%), where fire is thought to be inhibited due to the lack of light-demanding C4 grasses. Consequently, seedling survival under F. natalensis and B. floribunda was higher compared with the other two microsites. The seedling survival rate was similar under F. natalensis (57%) and B. floribunda (59%). However, only a few S. guineense ssp. afromontanum seedlings naturally established under B. floribunda (25/285) whereas many seedlings established under F. natalensis (146/285). These findings indicate that the facilitative mechanism of fire suppression is not the only factor affecting establishment. The seed deposition investigation revealed that most of the seeds (85%) were deposited under F. natalensis. As such, these findings suggest that in addition to fire suppression, dispersal limitations also play a role in forest-savannah dynamics in this region, especially at the community level.